Amulet: The Cloud Searchers - Book 3 Book three, The cloud searchers - Kibuishi, Kazu 1978- (New York : Graphix, 2010)
Naven, Emily and their crew of resistance fighters set off to find the lost city of Cielis and its' Guardian Council's Stonekeepers.
Keywords: Brothers and sisters -- Comic books, strips, etc; Amulets -- Comic books, strips, etc; Charms -- Comic books, strips, etc; Imaginary places -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Brothers and sisters -- Fiction; Amulets -- Fiction; Charms -- Fiction; Imaginary places -- Fiction; Magic -- Fiction; Fantasy comic books, strips, etc; Comic books, strips, etc; Graphic novels